Asynchronous pulse responses of soil carbon and nitrogen mineralization to rewetting events at a short-term: Regulation by microbes - Xiaoli Song (Nature Portfolio, 2017)
Abstract Rewetting after precipitation events plays an important role in regulating soil carbon (C) and nitrogen (N) turnover processes in arid and semiarid ecosystems. Here, we conducted a 48-h rewetting simulation experiment with measurements of soil C and N mineralization rates (R C and R N, respectively) and microbial biomass N (MBN) at high temporal resolution to explore the pulse responses of R C and R N. R C and R N responded strongly and rapidly to rewetting over the short term. The maximum R C value (because of pulse effects) ranged from 16.53 to 19.33 µg C gsoil −1 h−1, observed 10 min after rewetting. The maximum R N varied from 22.86 to 40.87 µg N gsoil −1 h−1, appearing 5–6 h after rewetting. The responses of soil microbial growth to rewetting were rapid, and the maximum MBN was observed 2–3 h after rewetting. Unexpectedly, there was no correlation between R C, R N, and MBN during the process of rewetting, and R C and R N were uncoupled. In sum, the pulse responses of R C, R N, and microbial growth to simulated rewetting were rapid, strong, and asynchronous, which offers insights into the different responses of microbes to rewetting and mechanisms behind microbes.